Shakespeare in Washington: From ’House of Cards’ to Capitol Hill - Pagetti, Carlo (Memoria di Shakespeare. A Journal of Shakespearean Studies, 2021)
In the twentieth century Shakespeare became a sort of incubator of mass culture and its formulaic genres. The history of Richard III enjoyed a popularity of its own: this Machiavellian dark lord was explored in an American context by Al Pacino in the movie Looking for Richard (1996), where one of the main characters, Buckingham, was acted by Kevin Spacey. Together with director Sam Mendes, Spacey, in the role of Richard Gloucester, made of Richard III the main performance in their ambitious Bridge Project (2011). The experience achieved by Spacey was crucial in the creation of the TV Netflix series House of Cards, conceived by Beau Willimon, whose pilot, directed by David Fincher, and aired on February 1, 2013, introduced the viewers to the deeds and misdeeds of the ambitious, scornful, ruthless American politician Frank Underwood, resolved to destroy enemies and friends in order to become President of the United States, explicitly a contemporary Richard Gloucester, also partly Iago, and partly Macbeth, supported by his wife Claire, interpreted by Robin Wright, a power-hungry Lady Macbeth.